Steady state temperatures in a quarter plane - B. D. Aggarwala; C. Nasim (International Journal of Mathematics and Mathematical Sciences)
The discontinuous boundary value problem of steady state temperatures in a quarter plane gives rise to a pair of dual integral equations which are not of Titchmarch type. These dual integral equations are considered in this paper.